Conditional trust: Community perceptions of drone use in malaria control in Zanzibar. (February 2022) - Hardy, Andy; Proctor, Mark; MacCallum, Cathryn; Shawe, Josh; Abdalla, Safia; Ali, Rajab; Abdalla, Salha; Oakes, Gregory; Rosu, Laura; Worrall, Eve
Abstract: Background: The potential of drones to support public health interventions, such as malaria vector control, is beginning to be realised. Although permissions from civil aviation authorities are often needed for drone operations, the communities over which they fly tend to be ignored: How do affected communities perceive drones? Is drone deployment accepted by communities? How should communities be engaged? Methods: An initiative in Zanzibar, United Republic of Tanzania is using drones to map malarial mosqutio breeding sites for targeting larval source management interventions. A community engagement framework was developed, based on participatory research, across three communities where drones will be deployed, to map local perceptions of drone use. Costs associated with this exercise were collated. Results: A total of 778 participants took part in the study spanning a range of community and stakeholder groups. Overall there was a high level of acceptance and trust in drone use for public health research purposes. Despite this level of trust for drone operations this support was conditional: There was a strong desire for pre-deployment information across all stakeholder groups and regular updates of this information to be given about drone activities, as well as consent from community level governance. The cost of the perception study and resulting engagement strategy was US$24, 411. Conclusions: Mapping and responding to community perceptions should be a pre-requisite for drone activity in all public health applications and requires funding. The findings made in this study were used to design a community engagement plan providing a simple but effective means of building and maintaining trust and acceptability. We recommend this an essential investment. Graphical abstract: Image 1 Highlights: There are a lack of studies into the community perceptions of drone use in a rural sub-Saharan setting. There is widespread trust in Zanzibar for the use of drones in public health but this trust comes with certain conditions. Communities need to be informed of drone activities and consent granted at the community level. Trust and consent for drone operations can be easily undone, especially where the use of this technology is unsolicited. Mapping community perceptions and establishing an engagement plan should be a pre-requisite for all drone operations.